Arbuscular Mycorrhizal Fungi and Biochar Improved Early Growth of Neem (Melia azedarach Linn.) Seedling Under Greenhouse Conditions - Sri Wilarso Budi; Luluk Setyaningsih (Institut Pertanian Bogor (IPB University), 2013)
The objective of this research was to determine the effect of biochar on the seedling quality index and growth of neem tree seedlings and arbuscular mycorrhizal fungi (AMF) development grown on ultisol soil medium. Two factors in completely randomised experimental design was conducted under green house conditions and Duncan Multiple Range Test was used to analyse the data. The results showed that neem seedling quality index was improved by interaction of AMF fungi and biochar amandment. The growth of neem seedling was significantly increased by interactions of arbuscular mycorrhizal fungi and biochar. The combination treatment of Glomus etunicatum and biochar 10% gave best results of height and diameter, and significantly increased by 712% and 303% respectively, as compared to control plant, while the combination treatment of Gigaspora margarita and biochar 10% gave the best result of shoot dry weight, and root dry weight and significantly increase by 4,547% and 6,957% as compared to control plant. The mycorrhizal root colonization was increased with increasing biochar added, but decreases when 15% of biochar was applied. N, P, and K uptake of 12 weeks neem seedling old was higher and significantly increased as compared to control plant.